Organizing Local Messengers: Working Conditions and Barriers to Unionization - Pupo, Norene; Noack, Andrea M. (Canadian Journal of Sociology, 2014)
As a result of concerns around declining memberships and the growth of precarious employment in recent years, unions have sought to expand their jurisdictions and organize groups of workers who have typically resisted collective bargaining. Research on union renewal has examined working conditions and workplace structures that may give rise to successful organizing campaigns. In this paper we examine working conditions amongst non-unionized same-day messengers working in Toronto, Canada. The research team conducted 143 semi-structured interviews with bikers, drivers and walkers who work primarily for local courier companies. We find that although same-day couriers are typically treated as ‘independent contractors’, they are dependent on brokers, and precariously employed, with unpredictable income and hours of work. Though this group would benefit substantially from unionization, especially organized on a sector-wide basis, their attitudes and culture combined with the structure of the local industry create substantial impediments to organizing.
Keywords: unionization